A techno-economic review of silicon photovoltaic module recycling. (July 2019) - Deng, Rong; Chang, Nathan L.; Ouyang, Zi; Chong, Chee Mun
Abstract: Even with a long lifetime of 25–30 years of green energy production, end-of-life treatment of solar photovoltaic modules can negatively impact the environment if not handled properly. This is particularly urgent when the use of photovoltaics has grown at an unprecedented rate, generating clean energy all over the world. Therefore, it is essential to develop commercially viable end-of-life recycling technologies to guarantee a sustainable future for the photovoltaic technology. Silicon photovoltaic modules, the most popular photovoltaic technology, have been shown to be economically unattractive for recycling - the materials are mixed and difficult to separate, and have low value, so that the cost of recycling is hardly recovered. In this paper, we review the state-of-art recycling technology and associate it with a quantitative economic assessment to breakdown the cost structure and better understand the presented economic barrier. The techno-economic review allows us to identify essential framework and technology changes required to overcome the current barrier to implementing commercial-scale recycling. (i) The authority may impose price signal to impress direct landfill of end-of-life modules while proactively establish an effective collection network. (ii) The local recyclers may aim at value recovery as a step beyond mass recovery, especially targeting at recovery of intact silicon wafers and silver to guarantee the recycling revenue. Meanwhile, efforts should be put on reducing the recycling processing cost. (iii) Photovoltaic module manufacturers may take end-of-life responsibilities and up-design the product to facilitate end-of-life recycling, which includes features for simple disassembly, recycling, and reducing or eliminating the use of toxic components. Highlights: Sustainable photovoltaic technology requires proper end-of-life management. The techno-economic analysis reveals new insights to overcome the economic barrier. Photovoltaic module recycling is a collaborative action among all stakeholders. Upcycling can achieve maximum environmental and economic benefits. Further technologies should aim at value recovery and up-front eco-design.